I problemi e le sfide della Russia nel mondo contemporaneo - Del Vecchio, Anna Maria (Studi Urbinati, A - Scienze giuridiche, politiche ed economiche, 2015)
The problems and challenges of Russia in the Eastern Europe area, the historical legacy, the political vision, the relations with the member states of USSR, the role of reality and ethnic-religious traditions are examined in this essay. I problemi e le sfide della Russia nello scacchiere dell’Europa orientale, l’eredità storica, la visione politica, i rapporti con gli Stati componenti dell’URSS, il ruolo delle realtà e tradizioni etnico-religiose.